2020
DOI: 10.1186/s13195-020-00687-2
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake and expenditure in patients with Alzheimer’s disease and mild cognitive impairment: the NUDAD project

Abstract: Background Malnutrition is common in patients with Alzheimer’s disease (AD) dementia and mild cognitive impairment (MCI) and is associated with institutionalization and increased mortality. Malnutrition is the result of a negative energy balance, which could be due to reduced dietary intake and/or higher energy expenditure. To study underlying mechanisms for malnutrition, we investigated dietary intake and resting energy expenditure (REE) of patients with AD dementia, MCI, and controls. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
2
18
1
Order By: Relevance
“…Since AD patients tend to lose weight over the course of the disease, it has been suggested that cognitive decline could lead to lower energy intake which might also affect microbiota composition ( 51 ). However, we have found previously that macronutrient intake was not different between diagnosis groups in this cohort ( 52 ). Moreover, associations between gut microbiota composition and AD biomarkers remained significant when adjusting for cognitive function (MMSE).…”
Section: Discussioncontrasting
confidence: 51%
“…Since AD patients tend to lose weight over the course of the disease, it has been suggested that cognitive decline could lead to lower energy intake which might also affect microbiota composition ( 51 ). However, we have found previously that macronutrient intake was not different between diagnosis groups in this cohort ( 52 ). Moreover, associations between gut microbiota composition and AD biomarkers remained significant when adjusting for cognitive function (MMSE).…”
Section: Discussioncontrasting
confidence: 51%
“…There is some controversy over contribution of energy expenditure on metabolic deficits in AD patients. While some studies show increased metabolism in AD [53], others indicate decreased or non-significant changes in energy expenditure (EE) in AD patients [54]. As previously seen, the Tg4510 and 3xTg mouse models of AD show a hypermetabolic state at an early age [13,46,55].…”
Section: Alterations In Food Intake and Energy Expenditure In 5xfad Micementioning
confidence: 87%
“…In line with this notion, we recently found a higher resting energy expenditure in patients with AD dementia compared with controls. 47 Future studies should further examine the potentially higher energy needs of patients with AD dementia.…”
Section: Discussionmentioning
confidence: 99%